Efektivitas Play Therapy dalam Pengendalian Emosi Anak Usia 3 sampai 5 Tahun - Ristra Sandra Ritonga; Rita Nofianti; Daud Arifin; Sabrina Patuzahra (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2024)
Early childhood is only able to express emotions by crying which in the end will become a tantrum in early childhood. One therapy that can be implemented is play therapy where children can easily express their emotions by playing, such as coloring and so on. This research was carried out using the meta analysis method so that the research results were obtained based on previous research. Meta analysis was carried out on eleven journals taken from Google Scholar and Eric Journal. The results of his research explained that almost all the journals that were used as informants for the results of his research explained that play therapy was very suitable for controlling the emotions of early childhood.